Negalyod. The god network - Perriot, Vincent, 1984- (Titan Comics, 2022)
"In a post-apocalyptic far future/alternate world, dinosaurs roam the desolate land, while the last denizens of humanity survive together in technological cities run by a military regime. Jarri, a loner who shepherds a group of dinosaurs, travels to the city when his herd is murdered. There he becomes involved with a rebel group who defy the totalitarian society, and uncovers a conspiracy that reveals the true nature of the world they live in. What he finds will change his life forever..."--Amazon.